Examining the relationship between complications and perioperative mortality following radical cystectomy: a population‐based analysis. (14th April 2019) - Mossanen, Matthew; Krasnow, Ross E.; Zlatev, Dimitar V.; Tan, Wei Shen; Preston, Mark A.; Trinh, Quoc‐Dien; Kibel, Adam S.; Sonpavde, Guru; Schrag, Deborah; Chung, Benjamin I.; Chang, Steven L.
Abstract : Objective: To examine the incidence of perioperative complications after radical cystectomy (RC) and assess their impact on 90‐day postoperative mortality during the index stay and upon readmission. Patients and methods: A total of 57 553 patients with bladder cancer (unweighted cohort: 9137 patients) treated with RC, at 360 hospitals in the USA between 2005 and 2013 within the Premier Healthcare Database, were used for analysis. The 90‐day perioperative mortality was the primary outcome. Multivariable regression was used to predict the probability of mortality; models were adjusted for patient, hospital, and surgical characteristics. Results: An increase in the number of complications resulted in an increasing predicted probability of mortality, with a precipitous increase if patients had four or more complications compared to one complication during hospitalisation following RC (index stay; 1.0–9.7%, P < 0.001) and during readmission (2.0–13.1%, P < 0.001). A readmission complication nearly doubled the predicted probability of postoperative mortality as compared to an initial complication (3.9% vs 7.4%, P < 0.001). During the initial hospitalisation cardiac‐ (odds ratio [OR] 3.1, 95% confidence interval [CI] 1.9–5.1), pulmonary‐ (OR 4.8, 95% CI 2.8–8.4), and renal‐related (OR 3.6, 95% CI 2–6.7) complications had the most significant impact on the odds of mortality across categories examined. Conclusions: The number and nature of complications have a distinct impact on mortality after RC. As complications increase there is an associated increase in perioperative mortality.